MHD flow of Williamson nanofluid using effective similarity variable considering viscous dissipation and thermal radiation over a non-linear stretching surface via OHAM - Muhammad Awais Sherani; Muhammad Sohail; Ibrahim Mahariq; Syed Tehseen Abbas (Partial Differential Equations in Applied Mathematics)
This work examines the 2D surface layer flow of Williamson Nano fluid across a non-linear extendable sheet utilizing magneto hydrodynamics (MHD), taking into account the impacts of heat generation(S), thermal radiation(Rd), chemical reaction(Cr), and viscous dissipation. This evaluation goes beyond the localized impacts usually taken into account in each linear and non-linear stretching scenario, and instead focuses on global impact of the not Newtonian Williamson fluid factor. The conservation laws of mass, momentum, and energy which are represented as partial differential equations form the foundation of the mathematical model. Using an appropriate similarity transformation, these equations are converted into ordinary differential equations, which can then be resolved numerically OHAM technique. The results depict the scenario in which with increasing values of λ and M, the velocity reduces because resistance is increased; meanwhile, the temperature profile is inversely proportional to higher Pr, Le, and Nbt, where it decreases because thermal diffusivity diminishes. Conversely, with an increase in Rd, Nc, and S, the thermal profiles augment. Concentration diminishes with the augmentation of Sc, Cr, and Nbt due to intensified Brownian motion and molecular interactions. It is observed that λ and M increase the value of skin friction, but −θ'(0), indicating heat transfer efficiency, increases with Pr, Le, and Nbt but declines with Rd and Nc. The mass transfer rate of −g'(0) is found to rise positively with Sc, Cr, and Nbt, which indicates an interacting relationship between the temperature and concentration fields in the fluid system.